Probing chiral Kitaev spin liquids via dangling boundary fermions - Shang-Shun Zhang; Gábor B. Halász; Cristian D. Batista (npj Quantum Materials)
Abstract Identifying experimental probes capable of diagnosing extreme quantum behavior is widely regarded as one of the foremost challenges in modern condensed matter physics. Here, we propose a novel approach for detecting chiral Kitaev spin-liquid states through measurements of the local dynamical spin structure factor on the boundary using scanning tunneling microscopy (STM). We specifically focus on unpaired (“dangling”) Majorana fermions, which naturally emerge along boundaries of Kitaev spin liquids, and can serve as indicators of chiral boundary modes under broad conditions, thereby offering a clear signature of these exotic quantum states.